Optimizing the Use of Microsoft Excel for Employees' Administrative Tasks at Le Premier Hotel Kota Deltamas, Cikarang - Weli Weli; Rilo Pambudi; Esther Meilia; Daniel Joshua (MITRA: Jurnal Pemberdayaan Masyarakat, 2021)
This community service activity was motivated by the needs of the employees at Le Premier Hotel, Kota Deltamas, Cikarang. They are mostly unfamiliar with Microsoft Excel and do not use it for data processing and completing their daily tasks. Microsoft Excel is an automated data processing application that can be used for various administrative purposes, from simple to complex ones. Forty employees of Le Premier Hotel participated in this program. Preliminary analysis results show that only a few employees can use Microsoft Excel while the ability to use this application is needed as the work volumes and the timeline for finishing the increase of the work. This activity aims to train the employees at Le Premier Hotel Kota Deltamas, Cikarang on how to use Microsoft Excel in completing their daily tasks. With this, it is hoped that they could complete their work more quickly and more accurately which will improve their work performance and skill. The method adopted in implementing this community service program is tutoring and hands-on training of Microsoft Excel using a computer or a laptop. The results are positive, i.e. adding knowledge and skills of how to use some basic operations for report preparation needs. The activities ran smoothly as scheduled. In addition, the activity was easily and comfortably held because all the participants had a laptop provided by the Le Premier Hotel Kota Deltamas, Cikarang. The participants claimed that this community service program has benefited them, and expected to get more advanced training to improve their capabilities in using Microsoft Excel and to facilitate them in completing their tasks.